Artistic spliced wood grain ceramic tile and preparation method thereof
By setting a glaze layer and pattern layer on the surface of the tiles and using a double-layer protective glaze layer, the problem of poor three-dimensional texture on the surface of existing artistic parquet wood grain tiles is solved, achieving higher artistic beauty and physical properties.
Patent Information
- Application Number
- CN202411851775.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
The three-dimensional surface texture of the existing artistic parquet wood grain tiles is poor, which is difficult to meet the aesthetic requirements and consumption needs of modern people.
By setting a surface glaze layer and a pattern layer on the surface of the tiles, the repulsive effect of functional ink and aqueous glaze slurry is used to form a depression wood grain texture, and a double-layer protective glaze layer is used to improve the stain resistance, slip resistance and wear resistance of the tiles.
It improves the artistic aesthetics and texture of the ceramic tile, bringing it close to the real solid wood art parquet floor, while enhancing its anti-fouling, anti-slip and wear resistance, meeting consumers' higher aesthetic and consumption needs.
Smart Images

Figure CN119684032A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to an artistic parquet wood-grain tile and a preparation method thereof. Background Art
[0002] Artistic parquet wood grain tiles are mostly used for floor decoration and wall decoration. They are generally in the upper middle level of the tile product grade and are one of the products selected for some mid-to-high-end decoration. Compared with ordinary wood grain tile products, artistic parquet wood grain tiles are more complex in terms of craftsmanship and technology. Wood grain patterns of different colors and textures are spliced on the surface of the tiles, making the tiles present various novel and beautiful shapes, and the appearance is more high-end and fashionable.
[0003] The artistic parquet wood grain tiles currently popular on the market are simply a simple combination of wood grain patterns of different colors and textures spliced together. Compared with parquet wood floors, the surface three-dimensional texture of existing artistic parquet wood grain tiles is poor, which is difficult to meet the aesthetic requirements and consumption needs of modern people. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an artistic parquet wood-grain tile with good fluorescent effect and a preparation method thereof.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] In a first aspect, the present invention provides an artistic parquet wood grain tile, comprising a brick blank, a glaze layer, and a pattern layer arranged in sequence, wherein the glaze layer has a concave wood grain texture, and the concave wood grain texture is prepared by the repulsive effect of functional ink and water-based glaze slurry;
[0007] The functional ink comprises the following components in parts by weight: 25 to 40 parts of a first frit, 14 to 22 parts of calcined alumina, 35 to 55 parts of an organic solvent, 3 to 8 parts of a dispersant, 2 to 4 parts of an etchant, and 1 to 3 parts of a hydrophobic agent;
[0008] The glaze in the aqueous glaze slurry includes the following components in parts by weight: 25-40 parts of potassium feldspar, 15-35 parts of sodium feldspar, 6-10 parts of calcined kaolin, 6-18 parts of calcined alumina, 4-15 parts of wollastonite, 6-18 parts of barium carbonate, 2-8 parts of strontium carbonate, 3-8 parts of zinc oxide, 3-12 parts of zirconium silicate, and 3-8 parts of second frit.
[0009] The present invention adopts matte glaze, solvent, dispersant, corrosive agent and hydrophobic agent to form a very hydrophobic oily mixture in proportion. The oily mixture can form a low-tension non-polar dense oil film on the surface of the brick, and then a highly polar and non-oleophilic water-based glaze slurry is applied on the surface of the tile with the oil film formed. In the area where the non-polar dense oil film is formed, the water-based glaze slurry is naturally repelled by the non-polar dense oil film, forming a relatively concave wood grain texture.
[0010] Preferably, the first frit comprises the following components in parts by weight: SiO2 55-60%, Al2O3 24-30%, K2O 1-3%, Na2O 2-5%, CaO 2-5%, ZnO 3-8%, BaO 1-3%, and B2O3 1-3%.
[0011] Further preferably, the first frit comprises the following components in mass percentage: SiO2 56.36-58.27%, Al2O3 25.94-27.18%, K2O 1.63-2.73%, Na2O 2.27-3.86%, CaO 2.52-3.22%, ZnO 3.46-4.07%, BaO 1.04-2.81%, and B2O3 1.07-2.49%.
[0012] The first frit used in the present invention has silicon dioxide and aluminum oxide as main components, and is compounded with appropriate amounts of potassium oxide, sodium oxide, calcium oxide, zinc oxide, barium oxide and boron trioxide. The first frit in the functional ink is compounded with calcined aluminum oxide in an appropriate proportion as a glaze component, which can ensure the matte effect of the glaze while improving the high temperature resistance of the glaze, stabilizing the firing temperature of the glaze, and widening the firing range of the glaze.
[0013] Preferably, the functional ink comprises the following components in parts by weight: 30-35 parts of a first frit, 16-18 parts of calcined alumina, 37-42 parts of an organic solvent, 5-7 parts of a dispersant, 3-3.5 parts of a corrosive agent, and 1.5-2 parts of a hydrophobic agent.
[0014] Preferably, the organic solvent includes at least one of triethylene glycol diisooctanoate, isopropyl laurate, isooctyl palmitate and fatty acid methyl ester; further preferably, the organic solvent includes the following components by weight: 35-45 parts of triethylene glycol diisooctanoate, 15-40 parts of isopropyl laurate, 15-35 parts of isooctyl palmitate and 15-25 parts of fatty acid methyl ester. Adding the above solvent to the functional ink can effectively promote the dissolution of the dispersant and the corrosive agent, which is beneficial to the uniform dissolution of each glaze component in the functional ink and ensures the overall uniformity of the functional ink.
[0015] Preferably, the dispersant includes one of sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate, and its function is to prevent the sedimentation and aggregation of ultrafine particles in the ink and promote the formation of a stable suspension.
[0016] Preferably, the corrosive agent includes at least one of bismuth vanadate, boron trioxide and sodium tetraborate. Bismuth vanadate, boron trioxide and sodium tetraborate are all low melting point compounds. During the high temperature firing process of ceramics, these low melting point compounds melt and volatilize, so that the tiles form a three-dimensional effect of slight corrosion depression.
[0017] Preferably, the hydrophobic agent includes at least one of organosilicon quaternary ammonium salt, fatty alcohol polyoxyethylene ether, and alkyl alcohol ether. Further preferably, the hydrophobic agent includes the following components in parts by weight: 1 to 10 parts of organosilicon quaternary ammonium salt, 1 to 10 parts of fatty alcohol polyoxyethylene ether, 10 to 20 parts of alkyl alcohol ether, and 60 to 88 parts of water. The present invention introduces a compound of organosilicon quaternary ammonium salt, fatty alcohol polyoxyethylene ether, alkyl alcohol ether and water, which can promote the dispersion effect of other components in the ink, form a stable dispersion, and make the functional ink have certain waterproof and hydrophobic properties.
[0018] Preferably, the glaze in the aqueous glaze slurry includes the following components in parts by weight: 28-32 parts of potassium feldspar, 17-20 parts of sodium feldspar, 6-8 parts of calcined kaolin, 6-10 parts of calcined alumina, 6-10 parts of wollastonite, 8-10 parts of barium carbonate, 3-5 parts of strontium carbonate, 4-6 parts of zinc oxide, 5-6 parts of zirconium silicate, and 4-6 parts of the second frit.
[0019] Preferably, the second frit comprises the following components in mass percentage: SiO2 45-55%, Al2O3 8-16%, K2O 3-9%, Na2O 1-3%, CaO 7-13%, MgO 0.5-2%, ZnO 4-8%, BaO 10-16%, and B2O3 2-5%.
[0020] Further preferably, the second frit comprises the following components in mass percentage: SiO2 48.52-51.69%, Al2O3 9.67-10.19%, K2O 4.48-5.08%, Na2O 1.26-2.63%, CaO 7.29-10.68%, MgO 0.93-1.65%, ZnO 5.56-6.52%, BaO 11.42-14.29%, and B2O3 2.11-3.62%.
[0021] The inventors have found through research that by rationally designing the formula of functional ink and the formula of glaze, the firing effect of tiles can be improved, and while ensuring the three-dimensional tactile effect of tiles, the anti-fouling, anti-slip and wear resistance of the tile glaze can be improved.
[0022] Preferably, the artistic parquet wood grain tile also includes a first protective glaze layer, which is covered on the pattern layer. The first protective glaze layer includes the following preparation raw materials in parts by weight: 30 to 55 parts of glaze powder, 40 to 60 parts of solvent, 3 to 7 parts of dispersant, 0 to 3 parts of surfactant, and 0 to 0.5 parts of anti-settling agent.
[0023] Further preferably, the glaze powder includes the following components in parts by weight: 15-30 parts of kaolin, 10-20 parts of illite, 8-16 parts of quartz powder, 6-15 parts of talc, 8-15 parts of dolomite, 3-10 parts of zirconium silicate, 6-10 parts of titanium dioxide, 3-15 parts of barium carbonate, and 0.5-1 part of sodium tripolyphosphate.
[0024] Further preferably, the artistic parquet wood grain tile also includes a second protective glaze layer, and the second protective glaze layer is covered on the first protective glaze layer.
[0025] Further preferably, the second protective glaze layer comprises the following preparation raw materials in parts by weight: 25-35 parts of potassium feldspar, 15-25 parts of sodium feldspar, 10-15 parts of calcined kaolin, 1-4 parts of washed ball clay, 8-15 parts of quartz powder, 5-15 parts of barium carbonate, 2-6 parts of zinc oxide, 10-20 parts of fluorite, 2-6 parts of the third frit, 0.2-0.5 parts of sodium tripolyphosphate, and 0.3-0.6 parts of sodium carboxymethyl cellulose; the third frit and the second frit are the same or different frit powders.
[0026] The present invention provides a double-layer protective glaze layer, which can not only effectively stabilize the color development effect of the wood grain texture color, but also improve various physical properties of the tile, such as anti-fouling, anti-slip and wear resistance.
[0027] Preferably, the pattern layer is formed by pattern ink.
[0028] It is understood that the present invention has no particular restrictions on the color of the pattern ink, and it can be formulated according to the desired wood grain pattern color. For example, every 10 ml of pattern ink includes 1.89 to 3.12 ml of blue ink, 1.03 to 2.93 ml of dark brown ink, 1.14 to 1.34 ml of wrapped yellow ink, 0.85 to 1.37 ml of black ink, 0.78 to 2.16 ml of beige ink, and 1.21 to 2.56 ml of wrapped red ink.
[0029] In a second aspect, the present invention provides a method for preparing the artistic parquet wood-grain tile as described in the first aspect, comprising the following steps:
[0030] S1, preparing bricks;
[0031] S2, printing functional ink on the brick according to the preset wood grain texture image;
[0032] S3, applying an aqueous glaze slurry on the surface of the brick blank printed with the functional ink, wherein the aqueous glaze slurry and the functional ink repel each other to form a concave wood grain texture, and a glaze layer is formed after drying;
[0033] S4, forming a pattern layer on a side of the glaze layer away from the brick according to a preset pattern;
[0034] S5, forming a first protective glaze layer on a side of the pattern layer away from the surface glaze layer;
[0035] S6, forming a second protective glaze layer on a side of the first protective glaze layer away from the first protective glaze layer to obtain a rough blank;
[0036] S7, grinding the edges of the rough blank after firing to obtain the artistic parquet wood-grain tile.
[0037] Preferably, in step S1, the moisture content of the brick is not greater than 0.3%, and the strength of the brick is not less than 1.8 MPa.
[0038] Preferably, in step S2, the functional ink is printed by inkjet printing, and during the inkjet printing process, the inkjet amount of the functional ink is 25-85 g / m 2 The temperature of the brick is 75-85°C.
[0039] In the present invention, the wood grain texture image may be at least one of mountain grain, straight grain, diagonal grain, staggered grain, bird's eye grain, large mountain grain, tree knot, tree branch, and ghost eye.
[0040] Preferably, in step S3, the water-based glaze slurry is applied by spraying, the specific gravity of the water-based glaze slurry is 1.45-1.55 g / mL, and the spraying weight of the water-based glaze slurry is 367-505 g / m 2 .
[0041] Preferably, in step S4, the pattern layer is formed by inkjet printing.
[0042] Preferably, in step S5, the first protective glaze layer is formed by inkjet printing, the inkjet printing grayscale corresponding to the first protective glaze layer is 10-50%, and the ink volume is 30-90 g / m 2 .
[0043] Preferably, in step S6, the second protective glaze layer is formed by spraying, the spray glaze specific gravity corresponding to the second protective glaze layer is 1.35-1.45 g / mL, and the spray glaze weight is 300-400 g / m 2 .
[0044] Preferably, in step S7, the firing temperature is 1200-1250° C., and the firing time is 40-90 min.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] The artistic parquet wood grain tiles provided by the present invention not only have the color composition effect of traditional parquet wood grain tiles, rich three-dimensionality, and a strong sense of heaviness, but also improve the artistic beauty and texture of the artistic parquet wood grain tiles, comparable to real solid wood artistic parquet wood floors. The artistic parquet wood grain tiles provided by the present invention also have excellent anti-fouling, anti-slip and wear resistance, and can meet consumers' higher aesthetic and consumption needs.
[0047] The preparation method of the invention is simple and efficient, the prepared finished product has good stability and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a physical picture of the ceramic tile obtained in Example 1;
[0049] Figure 2 This is a partial physical picture of the ceramic tile obtained in Example 1. DETAILED DESCRIPTION
[0050] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0051] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.
[0052] In the following embodiments and comparative examples, the bricks include the following components in mass percentage: SiO2 62.76%, Al2O3 21.42%, K2O 3.24%, Na2O 2.79%, CaO 2.72%, MgO 1.97%, Fe2O3 0.31%, TiO2 0.18%, and the remainder is loss on ignition and impurities.
[0053] Example 1
[0054] This embodiment provides an artistic parquet wood-grain tile, including a preparation method comprising:
[0055] S1, pressing the green body and drying the green body in a drying furnace at a temperature of 230° C. for 50 min to obtain a brick body;
[0056] S2. Print functional ink on the brick obtained in step S1 using an inkjet printer according to the preset wood grain texture pattern; the grayscale of the inkjet printer is set to 20%, the temperature of the brick is 80°C during printing, and the printing amount of the functional ink is 70g / m 2 ;
[0057] In step S2, the functional ink includes the following components in parts by weight: 30 parts of a first frit, 18 parts of calcined alumina, 42 parts of an organic solvent, 5 parts of a dispersant, 3 parts of an etchant, and 2 parts of a hydrophobic agent, wherein the first frit includes the following components in mass percentages: 56.36% SiO2, 25.94% Al2O3, 1.63% K2O, 3.74% Na2O, 2.98% CaO, 3.46% ZnO, 2.81% BaO, 2.49% B2O3, and other trace elements and impurity balances;
[0058] The particle size of the calcined alumina is a powder that passes through a 325 mesh sieve;
[0059] The organic solvent comprises the following components in parts by weight: 40 parts of triethylene glycol diisooctanoate, 20 parts of isopropyl laurate, 25 parts of isooctyl palmitate and 15 parts of fatty acid methyl ester;
[0060] The corrosive agent is bismuth vanadate;
[0061] The hydrophobic agent comprises the following components in parts by weight: 5 parts of organosilicon quaternary ammonium salt, 5 parts of fatty alcohol polyoxyethylene ether, 15 parts of alkyl alcohol ether and 75 parts of deionized water;
[0062] S3, using a swing-type high-pressure glaze spraying machine to spray water-based glaze slurry on the surface of the brick blank printed with functional ink, wherein the water-based glaze slurry and the functional ink repel each other to form a concave wood grain texture, and after drying, a glaze layer is formed;
[0063] In step S3, the specific gravity of the water-based glaze slurry is 1.46 g / mL, and the spray glaze weight is 413 g / m 2 The water-based glaze slurry is made by mixing glaze and water and then grinding. The solid content of the water-based glaze slurry is 46.5%, and the fineness is 0.25g / 100g slurry (passing a 325-mesh standard sieve); the glaze includes the following raw materials in parts by weight: 28 parts of potassium feldspar, 17 parts of sodium feldspar, 8 parts of calcined kaolin, 10 parts of calcined alumina, 6 parts of wollastonite, 10 parts of barium carbonate, 3 parts of strontium carbonate, 6 parts of zinc oxide, 6 parts of zirconium silicate, and 6 parts of the second frit; the second frit includes the following components in mass percentage: SiO2 50.34%, Al2O3 10.16%, K2O 4.52%, Na2O 1.26%, CaO 9.86%, MgO 0.93%, ZnO 5.56%, BaO 14.29%, B2O3 2.44%, and other trace elements and impurities remainder;
[0064] S4, using an inkjet printer to print pattern ink on the side of the glaze layer away from the brick, and forming a pattern layer on the glaze layer after drying; the printing ink volume of the pattern ink is 10ml / m2 Each 10 mL of pattern ink is prepared from the following components: 3.12 ml of CXN-11012 blue ink (Tao Lixi), 1.03 ml of CXN-55166 dark brown ink (Tao Lixi), 1.14 ml of NGY82012 wrapped yellow ink (Yangzi), 1.37 ml of CXN-40118 black ink (Tao Lixi), 0.78 ml of CXN-31929 beige ink (Tao Lixi) and 2.56 ml of NGY82016 wrapped red ink (Yangzi);
[0065] S5, using an inkjet printer to print digital protective glaze ink on the pattern layer, and after drying, forming a first protective glaze layer;
[0066] In step S5, the dual-channel grayscale value of the inkjet printer is 20%, and the printing ink volume of the digital protective glaze ink is 40g / m 2 ; The digital protection glaze ink includes the following components in parts by weight: 40 parts of ultrafine glaze powder, 52 parts of solvent, 5 parts of dispersant, 2.8 parts of surfactant, 0.2 parts of anti-settling agent, and the ultrafine glaze powder includes the following components in parts by weight: 25 parts of kaolin, 15 parts of illite, 14 parts of quartz powder, 12 parts of talc, 13 parts of dolomite, 4.5 parts of zirconium silicate, 10 parts of titanium dioxide, 6 parts of barium carbonate, and 0.5 parts of sodium tripolyphosphate;
[0067] The solvent is ethanol;
[0068] The dispersant is sodium tripolyphosphate;
[0069] The surfactant is sorbitan fatty acid ester;
[0070] The anti-settling agent is polyamide wax;
[0071] S6, using an Airpower high-pressure spray gun to spray the protective glaze slurry on the first protective glaze layer, forming a second protective glaze layer after drying, and obtaining a rough blank;
[0072] In step S6, the spray gun pressure is 8 bar, the spray glaze specific gravity of the protective glaze slurry is 1.38 g / mL, and the spray glaze weight is 350 g / m 2 The protective glaze slurry is made by mixing a protective glaze and water and then grinding them. The solid content of the protective glaze slurry is 41%, and the fineness is 0.25g / 100g slurry (passing through a 325-mesh standard sieve). The protective glaze comprises the following components in parts by weight: 30 parts of potassium feldspar, 20 parts of sodium feldspar, 12 parts of calcined kaolin, 2 parts of washed ball clay, 10 parts of quartz powder, 8 parts of barium carbonate, 2 parts of zinc oxide, 13 parts of fluorite, 3 parts of the third frit, 0.2 parts of sodium tripolyphosphate, and 0.3 parts of sodium carboxymethyl cellulose; the third frit has the same formula as the second frit in step S3;
[0073] S7, firing the rough blank at 1250° C. for 40 min, and grinding the edges to obtain the artistic parquet wood-grain ceramic tile.
[0074] Example 2
[0075] The difference between this embodiment and Embodiment 1 is that the functional ink of this embodiment includes the following components in parts by weight: 35 parts of a first frit, 16 parts of calcined alumina, 37 parts of an organic solvent, 7 parts of a dispersant, 3.5 parts of a corrosive agent, and 1.5 parts of a hydrophobic agent, and the first frit includes the following components in mass percentages: SiO2 57.66%, Al2O3 27.18%, K2O 2.55%, Na2O 2.27%, CaO 3.22%, ZnO 3.52%, BaO 1.45%, B2O3 1.67%, and other trace elements and impurities as remainder.
[0076] Example 3
[0077] The difference between this embodiment and embodiment 1 is that the functional ink of this embodiment includes the following components in parts by weight: 25 parts of a first melt, 14 parts of calcined alumina, 55 parts of an organic solvent, 3 parts of a dispersant, 2 parts of a corrosive agent, and 1 part of a hydrophobic agent.
[0078] Example 4
[0079] The difference between this embodiment and embodiment 1 is that the functional ink of this embodiment includes the following components in parts by weight: 40 parts of a first melt, 19 parts of calcined alumina, 35 parts of an organic solvent, 8 parts of a dispersant, 4 parts of a corrosive agent, and 3 parts of a hydrophobic agent.
[0080] Example 5
[0081] The difference between this embodiment and Example 1 is that the glaze of this embodiment includes the following raw materials in parts by weight: 32 parts of potassium feldspar, 20 parts of sodium feldspar, 6 parts of calcined kaolin, 6 parts of calcined alumina, 10 parts of wollastonite, 8 parts of barium carbonate, 5 parts of strontium carbonate, 4 parts of zinc oxide, 5 parts of zirconium silicate, and 4 parts of the second melt.
[0082] Example 6
[0083] The difference between this embodiment and Example 1 is that the glaze of this embodiment includes the following raw materials in parts by weight: 25 parts of potassium feldspar, 35 parts of sodium feldspar, 6 parts of calcined kaolin, 6 parts of calcined alumina, 15 parts of wollastonite, 18 parts of barium carbonate, 2 parts of strontium carbonate, 3 parts of zinc oxide, 12 parts of zirconium silicate, and 3 parts of the second melt.
[0084] Example 7
[0085] The difference between this embodiment and Example 1 is that the glaze of this embodiment includes the following raw materials in parts by weight: 40 parts of potassium feldspar, 15 parts of sodium feldspar, 10 parts of calcined kaolin, 18 parts of calcined alumina, 4 parts of wollastonite, 6 parts of barium carbonate, 8 parts of strontium carbonate, 8 parts of zinc oxide, 3 parts of zirconium silicate, and 8 parts of the second melt.
[0086] Example 8
[0087] This embodiment provides an artistic parquet wood-grain tile, including a preparation method comprising:
[0088] S1. Prepare a brick according to step S1 of Example 1;
[0089] S2. Print functional ink on the brick obtained in step S1 using an inkjet printer according to the preset wood grain texture pattern; the grayscale of the inkjet printer is set to 32%, the temperature of the brick is 75°C during printing, and the printing amount of the functional ink is 85g / m 2 ;
[0090] In step S2, the functional ink includes the following components in parts by weight: 30 parts of a first frit, 18 parts of calcined alumina, 42 parts of an organic solvent, 5 parts of a dispersant, 3 parts of a corrosive agent, and 2 parts of a hydrophobic agent. The first frit includes the following components in mass percentages: 58.27% SiO2, 26.45% Al2O3, 2.51% K2O, 2.92% Na2O, 3.08% CaO, 3.86% ZnO, 1.23% BaO, 1.07% B2O3, and other trace elements and impurity remainders.
[0091] The particle size of the calcined alumina is 325 mesh;
[0092] The organic solvent comprises the following components in parts by weight: 35 parts of triethylene glycol diisooctanoate, 40 parts of isopropyl laurate, 15 parts of isooctyl palmitate and 25 parts of fatty acid methyl ester;
[0093] The corrosive agent is bismuth vanadate;
[0094] The hydrophobic agent comprises the following components in parts by weight: 1 part of organosilicon quaternary ammonium salt, 1 part of fatty alcohol polyoxyethylene ether, 20 parts of alkyl alcohol ether and 78 parts of deionized water;
[0095] S3, using a swing-type high-pressure glaze spraying machine to spray water-based glaze slurry on the surface of the brick blank printed with functional ink, wherein the water-based glaze slurry and the functional ink repel each other to form a concave wood grain texture, and a glaze layer is formed after drying;
[0096] In step S3, the spraying specific gravity of the water-based glaze slurry is 1.45 g / mL, and the spraying weight is 367 g / m 2The water-based glaze slurry is made by mixing glaze and water and then grinding. The solid content of the water-based glaze slurry is 46%, and the fineness is 0.4g / 100g slurry (passing through a 325-mesh standard sieve); the glaze includes the following raw materials in parts by weight: 28 parts of potassium feldspar, 17 parts of sodium feldspar, 8 parts of calcined kaolin, 10 parts of calcined alumina, 6 parts of wollastonite, 10 parts of barium carbonate, 3 parts of strontium carbonate, 6 parts of zinc oxide, 6 parts of zirconium silicate, and 6 parts of the second frit; the second frit includes the following components in mass percentage: SiO2 48.52%, Al2O39.67%, K2O 4.48%, Na2O 2.63%, CaO10.68%, MgO1.65%, ZnO6.52%, BaO 11.42%, B2O33.62%, and other trace elements and impurity remainders.
[0097] S4, using an inkjet printer to print pattern ink on the glaze layer, and forming a pattern layer on the glaze layer after drying; the ink volume of the pattern ink is 10mL / m 2 Each 10 mL of pattern ink is prepared from the following components: CXN-11012 blue ink (Tao Lixi) 2.15 ml, CXN-55166 dark brown ink (Tao Lixi) 2.06 ml, NGY82012 wrapped yellow ink (Yangzi) 1.34 ml, CXN-40118 black ink (Tao Lixi) 1.08 ml, CXN-31929 beige ink (Tao Lixi) 2.16 ml and NGY82016 wrapped red ink (Yangzi) 1.21 ml;
[0098] S5, using an inkjet printer to print digital protective glaze ink on the pattern layer, and after drying, a first protective glaze layer is formed on the pattern layer;
[0099] In step S5, the dual-channel grayscale value of the inkjet printer is 10%, and the printing ink volume of the digital protective glaze ink is 30g / m 2 ; The digital protection glaze ink includes the following components in parts by weight: 30 parts of glaze powder, 40 parts of solvent, 3 parts of dispersant, 1 part of surfactant, and 0.1 part of anti-settling agent; The glaze powder includes the following components in parts by weight: 15 parts of kaolin, 20 parts of illite, 16 parts of quartz powder, 6 parts of talc, 8 parts of dolomite, 12 parts of zirconium silicate, 10 parts of titanium dioxide, 3 parts of barium carbonate, and 1 part of sodium tripolyphosphate;
[0100] The solvent is ethanol;
[0101] The dispersant is sodium hexametaphosphate;
[0102] The surfactant is sorbitan fatty acid ester;
[0103] The anti-settling agent is polyamide wax;
[0104] S6, spraying the protective glaze slurry onto the first protective glaze layer using an Airpower high-pressure spray gun, and forming a second protective glaze layer on the first protective glaze layer after drying to obtain a rough blank;
[0105] In step S6, the spray gun pressure is 8 bar, the spray glaze specific gravity of the protective glaze slurry is 1.45 g / mL, and the spray glaze weight is 400 g / m 2 The protective glaze slurry is made by mixing the protective glaze and water and then grinding them. The solid content of the protective glaze slurry is 45%, and the fineness is 0.3g / 100g slurry (passing through a 325-mesh standard sieve). The protective glaze includes the following components in parts by weight: 25 parts of potassium feldspar, 25 parts of sodium feldspar, 15 parts of calcined kaolin, 1 part of washed ball clay, 8 parts of quartz powder, 15 parts of barium carbonate, 2 parts of zinc oxide, 20 parts of fluorite, 2 parts of the third frit, 0.2 parts of sodium tripolyphosphate, and 0.3 parts of sodium carboxymethyl cellulose;
[0106] The formula of the third frit is the same as the formula of the second frit in step S3;
[0107] S7, firing the rough blank at 1240° C. for 50 min, and grinding the edges to obtain the artistic parquet wood-grain ceramic tile.
[0108] Example 9
[0109] This embodiment provides an artistic parquet wood-grain tile, including a preparation method comprising:
[0110] S1. Prepare a brick according to step S1 of Example 1;
[0111] S2. Print functional ink on the brick obtained in step S1 using an inkjet printer according to the preset wood grain texture pattern; the grayscale of the inkjet printer is set to 20%, the temperature of the brick is 75°C during printing, and the printing amount of the functional ink is 50g / m 2 ;
[0112] In step S2, the functional ink includes the following components in parts by weight: 30 parts of a first frit, 18 parts of calcined alumina, 42 parts of an organic solvent, 5 parts of a dispersant, 3 parts of an etchant, and 2 parts of a hydrophobic agent, wherein the first frit includes the following components in mass percentages: 57.14% SiO2, 26.51% Al2O3, 2.73% K2O, 3.86% Na2O, 2.52% CaO, 4.07% ZnO, 1.04% BaO, 2.11% B2O3, and other trace elements and impurity balances;
[0113] The particle size of the calcined alumina is 325 mesh;
[0114] The organic solvent comprises the following components in parts by weight: 40 parts of triethylene glycol diisooctanoate, 20 parts of isopropyl laurate, 25 parts of isooctyl palmitate and 15 parts of fatty acid methyl ester;
[0115] The corrosive agent is bismuth vanadate;
[0116] The hydrophobic agent comprises the following components in parts by weight: 5 parts of organosilicon quaternary ammonium salt, 5 parts of fatty alcohol polyoxyethylene ether, 15 parts of alkyl alcohol ether and 75 parts of deionized water;
[0117] S3, using a swing-type high-pressure glaze spraying machine to spray water-based glaze slurry on the surface of the brick blank printed with functional ink, wherein the water-based glaze slurry and the functional ink repel each other to form a concave wood grain texture, and a glaze layer is formed after drying;
[0118] In step S3, the spraying specific gravity of the water-based glaze slurry is 1.55 g / mL, and the spraying weight is 505 g / m 2 The water-based glaze slurry is made by mixing glaze and water and then grinding. The solid content of the water-based glaze slurry is 52.5%, and the fineness is 0.2g / 100g slurry (passing through a 325-mesh standard sieve); the glaze includes the following raw materials in parts by weight: 28 parts of potassium feldspar, 17 parts of sodium feldspar, 8 parts of calcined kaolin, 10 parts of calcined alumina, 6 parts of wollastonite, 10 parts of barium carbonate, 3 parts of strontium carbonate, 6 parts of zinc oxide, 6 parts of zirconium silicate, and 6 parts of the second frit; the second frit includes the following components in mass percentage: SiO2 51.69%, Al2O3 10.19%, K2O 5.08%, Na2O 1.65%, CaO 7.29%, MgO 1.45%, ZnO 6.19%, BaO13.62%, B2O3 2.11%, and other trace elements and impurity remainders.
[0119] S4, using an inkjet printer to print pattern ink on the glaze layer, and forming a pattern layer on the glaze layer after drying; the ink volume of the pattern ink is 10mL / m 2 Each 10 mL of pattern ink is prepared from the following components: CXN-11012 blue ink (Tao Lixi) 1.89 ml, CXN-55166 dark brown ink (Tao Lixi) 2.93 ml, NGY82012 wrapped yellow ink (Yangzi) 1.24 ml, CXN-40118 black ink (Tao Lixi) 0.85 ml, CXN-31929 beige ink (Tao Lixi) 1.27 ml and NGY82016 wrapped red ink (Yangzi) 1.82 ml;
[0120] S5, using an inkjet printer to print digital protective glaze ink on the pattern layer, and after drying, a first protective glaze layer is formed on the pattern layer;
[0121] In step S5, the dual-channel grayscale value of the inkjet printer is 50%, and the printing ink volume of the digital protective glaze ink is 90g / m 2 ; The digital protection glaze ink includes the following components in parts by weight: 55 parts of glaze powder, 60 parts of solvent, 7 parts of dispersant, 3 parts of surfactant, and 0.5 parts of anti-settling agent; The glaze powder includes the following components in parts by weight: 30 parts of kaolin, 10 parts of illite, 8 parts of quartz powder, 15 parts of talc, 15 parts of dolomite, 8 parts of zirconium silicate, 6 parts of titanium dioxide, 6 parts of barium carbonate, and 3 parts of sodium tripolyphosphate;
[0122] The solvent is ethanol;
[0123] The dispersant is sodium pyrophosphate;
[0124] The surfactant is sorbitan fatty acid ester;
[0125] The anti-settling agent is polyamide wax;
[0126] S6, using an Airpower high-pressure spray gun to spray the protective glaze slurry on the first protective glaze layer, forming a second protective glaze layer after drying, and obtaining a rough blank;
[0127] In step S6, the spray gun pressure is 8 bar, the spray glaze specific gravity of the protective glaze slurry is 1.35 g / mL, and the spray glaze weight is 300 g / m 2 The protective glaze slurry is made by mixing a protective glaze and water and then grinding them. The solid content of the protective glaze slurry is 40%, and the fineness is 0.35g / 100g slurry (passing through a 325-mesh standard sieve). The protective glaze includes the following components in parts by weight: 35 parts of potassium feldspar, 15 parts of sodium feldspar, 10 parts of calcined kaolin, 4 parts of washed ball clay, 15 parts of quartz powder, 5 parts of barium carbonate, 6 parts of zinc oxide, 10 parts of fluorite, 6 parts of the third frit, 0.5 parts of sodium tripolyphosphate, and 0.6 parts of sodium carboxymethyl cellulose; the frit in the protective glaze has the same formula as the second frit in step S3;
[0128] S7, firing the rough blank at 1200° C. for 70 min, and grinding the edges to obtain the artistic parquet wood-grain ceramic tile.
[0129] Comparative Example 1
[0130] The difference between this comparative example and Example 1 is that this comparative example further comprises in step S1: using a swing-type high-pressure glaze spraying machine to spray water-based base glaze slurry on the surface of the dried brick blank to form a brick blank covered with a base glaze layer; the water-based base glaze slurry and the water-based top glaze slurry in step S3 are slurries with the same formula, and the spraying weight of the water-based base glaze slurry is 413g / m 2 .
[0131] Comparative Example 2
[0132] The difference between this comparative example and Example 1 is that in this comparative example, the weight percentage of the first frit in the functional ink is 45 parts.
[0133] Comparative Example 3
[0134] The difference between this comparative example and Example 1 is that in this comparative example, the weight proportion of the first frit in the functional ink is 20 parts.
[0135] Comparative Example 4
[0136] The difference between this comparative example and Example 1 is that in this comparative example, "30 parts of first melt and 18 parts of calcined alumina" in the raw materials for preparing the texture layer are replaced with "48 parts of glaze", and the glaze has the same formula as the top glaze in step S3 of Example 1.
[0137] Comparative Example 5
[0138] The difference between this comparative example and Example 1 is that in this comparative example, the weight portion of the corrosive agent in the functional ink is 5 parts.
[0139] Comparative Example 6
[0140] The difference between this comparative example and Example 1 is that the second frit is not used in step S3 of this comparative example, and the frit used in step S3 has the same formula as the first frit in step S2.
[0141] Comparative Example 7
[0142] The difference between this comparative example and Example 1 is that the ceramic tile of this comparative example is not provided with a second protective glaze layer.
[0143] Comparative Example 8
[0144] The difference between this comparative example and Example 1 is that the ceramic tile of this example is not provided with the first protective glaze layer.
[0145] Effect Example 1
[0146] The tiles prepared in Examples 1 to 9 and Comparative Examples 1 to 8 were used as test samples and the following tests were performed:
[0147] (1) Evaluation of three-dimensional touch effect: Invite R&D personnel and tile sales personnel in the industry to form an evaluation team to evaluate the surface of the sample. The evaluation results are given by the evaluation team after discussion. The evaluation team members touch the glaze surface with their hands and divide it into three grades: excellent, medium and inferior. The glaze effect is excellent if it feels close to the real solid wood art parquet floor, with rich three-dimensionality and a strong sense of heaviness; the glaze surface has a slight three-dimensional feeling and is slightly rough, which is medium; the glaze surface is smooth or the glaze surface has obvious transitions and unevenness (giving people an uncomfortable rough feeling), which is inferior;
[0148] (2) Antifouling property: Test in accordance with GB / T3810.14-2016. The staining agent is brought into contact with the glaze surface of the sample and allowed to act for a certain period of time. The sample is then cleaned according to the prescribed cleaning method and the visible changes in the glaze surface of the sample are observed to determine the stain resistance of the sample.
[0149] (3) Anti-slip property: The test is conducted in accordance with GB / T35153-2017. A pendulum with a certain potential energy is swung across the surface of the specimen for a specified distance and then to the other side. The anti-slip property of the specimen surface is evaluated by the potential energy lost by the pendulum in overcoming the frictional resistance of the specimen surface during this process.
[0150] (4) Wear resistance: Tested in accordance with GB / T3810.7-2016. The wear resistance of the glaze is determined by placing abrasive media on the glaze surface and rotating it. The worn samples are compared with the unworn samples to evaluate the wear resistance of the ceramic tile. The samples are divided into Grade 0, Grade 1, Grade 2, Grade 3, Grade 4 and Grade 5.
[0151] The test results are shown in Table 1. The actual photos of the tiles prepared in Example 1 are shown in Table 1. Figures 1-2 shown.
[0152] Table 1
[0153]
[0154] From Table 1 and Figures 1-2 It can be seen that the three-dimensional tactile effect of the tiles prepared in Examples 1 to 9 is close to that of real solid wood artistic parquet flooring, with rich three-dimensionality and a strong sense of thickness, and has excellent anti-fouling, anti-slip and wear resistance. The anti-fouling level reaches level 5 (the highest level), the anti-slip value BPN is greater than the national standard 35, and the wear resistance level reaches level 4.
[0155] Compared with Example 1, in Comparative Example 1, a base glaze layer is formed on the brick blank, and functional ink is printed on the base glaze layer, so that the prepared ceramic tile is smoother, the three-dimensional tactile effect of the ceramic tile is weakened, and the wear resistance is deteriorated.
[0156] Compared with Example 1, the amount of the first frit added to the functional ink used in Comparative Example 2 is too much, so that the firing temperature is lower than the firing temperature of the glaze in the functional ink, which causes the touch of the tile to become noticeably rougher and the anti-fouling performance to be significantly reduced.
[0157] Compared with Example 1, the amount of the first melt added in the functional ink used in Comparative Example 3 is too small, so that the firing temperature is significantly higher than the firing temperature of the glaze in the functional ink, which in turn causes the tile to feel smoother and the anti-slip and wear resistance are significantly reduced.
[0158] Compared with Example 1, the glaze of the functional ink in Comparative Example 4 is the same as the glaze of the water-based glaze slurry, resulting in the tile having a smoother touch, and significantly reduced anti-slip and wear resistance.
[0159] Compared with Example 1, the amount of corrosive agent used in the functional ink of Comparative Example 5 is too much, and too much corrosive agent volatilizes during the firing process, resulting in an overly obvious texture transition on the surface of the tile, giving people an uncomfortable rough feeling, and the anti-fouling performance is significantly deteriorated.
[0160] Compared with Example 1, in Comparative Example 6, the frit in the aqueous glaze slurry of step S3 has the same composition as the first frit in step S2, resulting in poor firing effect, weakened three-dimensional touch of the prepared tiles, and significantly poor anti-fouling performance.
[0161] Compared with Example 1, Comparative Example 7 does not have a second protective glaze layer, and Comparative Example 8 does not have a first protective glaze layer, which results in a weakened three-dimensional touch of the tile, and poor anti-fouling, anti-slip and wear resistance.
[0162] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An artistic parquet wood grain tile, characterized in that: It comprises a brick blank, a glaze layer and a pattern layer which are arranged in sequence, wherein the glaze layer has a concave wood grain texture, and the concave wood grain texture is prepared by the repulsive effect of functional ink and water-based glaze slurry; The functional ink comprises the following components in parts by weight: 25 to 40 parts of a first frit, 14 to 22 parts of calcined alumina, 35 to 55 parts of an organic solvent, 3 to 8 parts of a dispersant, 2 to 4 parts of an etchant, and 1 to 3 parts of a hydrophobic agent; The glaze in the aqueous glaze slurry includes the following components in parts by weight: 25-40 parts of potassium feldspar, 15-35 parts of sodium feldspar, 6-10 parts of calcined kaolin, 6-18 parts of calcined alumina, 4-15 parts of wollastonite, 6-18 parts of barium carbonate, 2-8 parts of strontium carbonate, 3-8 parts of zinc oxide, 3-12 parts of zirconium silicate, and 3-8 parts of second frit.
2. The artistic parquet wood-grain tile according to claim 1, characterized in that: The first frit includes the following components in mass percentage: SiO2 55-60%, Al2O3 24-30%, K2O 1-3%, Na2O 2-5%, CaO 2-5%, ZnO 3-8%, BaO 1-3%, and B2O3 1-3%.
3. The artistic parquet wood-grain tile according to claim 1, characterized in that: The second frit includes the following components in mass percentage: SiO2 45-55%, Al2O3 8-16%, K2O 3-9%, Na2O 1-3%, CaO 7-13%, MgO0.5-2%, ZnO 4-8%, BaO 10-16%, and B2O3 2-5%.
4. The artistic parquet wood-grain tile according to claim 1, characterized in that: The organic solvent comprises at least one of triethylene glycol diisooctanoate, isopropyl laurate, isooctyl palmitate and fatty acid methyl ester; The dispersant includes one of sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate; The corrosive agent includes at least one of bismuth vanadate, boron trioxide, and sodium tetraborate; The hydrophobic agent includes at least one of organosilicon quaternary ammonium salt, fatty alcohol polyoxyethylene ether, and alkyl alcohol ether.
5. The artistic parquet wood-grain tile according to claim 1, characterized in that: It also includes a first protective glaze layer, which is covered on the pattern layer. The first protective glaze layer includes the following preparation raw materials in parts by weight: 30 to 55 parts of glaze powder, 40 to 60 parts of solvent, 3 to 7 parts of dispersant, 0 to 3 parts of surfactant, and 0 to 0.5 parts of anti-settling agent.
6. The artistic parquet wood-grain tile according to claim 5, characterized in that: The glaze powder comprises the following components in parts by weight: 15-30 parts of kaolin, 10-20 parts of illite, 8-16 parts of quartz powder, 6-15 parts of talc, 8-15 parts of dolomite, 8-12 parts of zirconium silicate, 6-10 parts of titanium dioxide, 3-6 parts of barium carbonate and 1-3 parts of sodium tripolyphosphate.
7. The artistic parquet wood-grain tile according to claim 5, characterized in that: It also includes a second protective glaze layer, wherein the second protective glaze layer covers the first protective glaze layer.
8. The artistic parquet wood-grain tile according to claim 7, characterized in that: The second protective glaze layer includes the following preparation raw materials in parts by weight: 25-35 parts of potassium feldspar, 15-25 parts of sodium feldspar, 10-15 parts of calcined kaolin, 1-4 parts of washed ball clay, 8-15 parts of quartz powder, 5-15 parts of barium carbonate, 2-6 parts of zinc oxide, 10-20 parts of fluorite, 2-6 parts of the third frit, 0.2-0.5 parts of sodium tripolyphosphate, and 0.3-0.6 parts of sodium carboxymethyl cellulose; the third frit and the second frit are the same or different frit powders.
9. A method for preparing the artistic parquet wood-grain tile according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, preparing bricks; S2, printing functional ink on the brick according to the preset wood grain texture image; S3, applying an aqueous glaze slurry on the surface of the brick blank printed with the functional ink, wherein the aqueous glaze slurry and the functional ink repel each other to form a concave wood grain texture, and a glaze layer is formed after drying; S4, forming a pattern layer on a side of the glaze layer away from the brick according to a preset pattern; S5, forming a first protective glaze layer on a side of the pattern layer away from the surface glaze layer; S6, forming a second protective glaze layer on a side of the first protective glaze layer away from the first protective glaze layer to obtain a rough blank; S7, grinding the edges of the rough blank after firing to obtain the artistic parquet wood-grain ceramic tile.
10. The method for preparing the artistic parquet wood-grain tile according to claim 9, characterized in that: In step S2, the functional ink is printed by inkjet printing. During the inkjet printing process, the inkjet amount of the functional ink is 25-85 g / m 2 The temperature of the brick is 75-85°C.
Citation Information
Cited By
High-proportion reclaimed material low-temperature quick-firing ceramic and preparation method thereof
CN119430858A
A high-proportion recycled material low-temperature rapid-firing ceramic and its preparation method
CN119430858B